Efficacy of cognitive‐behavioral group therapy in patients at risk for serious mental illness presenting with subthreshold bipolar symptoms: Results from a prespecified interim analysis of a multicenter, randomized, controlled study. (13th March 2020) - Leopold, Karolina; Bauer, Michael; Bechdolf, Andreas; Correll, Christoph U.; Holtmann, Martin; Juckel, Georg; Lambert, Martin; Meyer, Thomas D.; Pfeiffer, Steffi; Kittel‐Schneider, Sarah; Reif, Andreas; Stamm, Thomas J.; et al.
Abstract: Objective: Most patients with bipolar disorders (BD) exhibit prodromal symptoms before a first (hypo)manic episode. Patients with clinically significant symptoms fulfilling at‐risk criteria for serious mental illness (SMI) require effective and safe treatment. Cognitive‐behavioral psychotherapy (CBT) has shown promising results in early stages of BD and in patients at high risk for psychosis. We aimed to investigate whether group CBT can improve symptoms and functional deficits in young patients at risk for SMI presenting with subthreshold bipolar symptoms. Method: In a multicenter, randomized, controlled trial, patients at clinical risk for SMI presenting with subthreshold bipolar symptoms aged 15‐30 years were randomized to 14 weeks of at‐risk for BD‐specific group CBT or unstructured group meetings. Primary efficacy endpoints were differences in affective symptomatology and psychosocial functioning at 14 weeks. At‐risk status was defined as a combination of subthreshold bipolar symptomatology, reduction of psychosocial functioning and a family history for (schizo)affective disorders. A prespecified interim analysis was conducted at 75% of the targeted sample. Results: Of 128 screened participants, 75 were randomized to group CBT (n = 38, completers = 65.8%) vs unstructured group meetings (n = 37, completers = 78.4%). Affective symptomatology and psychosocial functioning improved significantly at week 14 ( P  < .001) and during 6 months ( P  < .001) in both groups, without significant between‐group differences. Findings are limited by the interim character of the analysis, the use of not fully validated early detection interviews, a newly adapted intervention manual, and the substantial drop‐outs. Conclusions: Results suggest that young patients at‐risk for SMI presenting with subthreshold bipolar symptoms benefit from early group sessions. The degree of specificity and psychotherapeutic interaction needed requires clarification.